Safety and Efficacy of Diluted Calcium Hydroxylapatite for the Treatment of Cellulite Dimpling on the Buttocks: Results from an Open-Label, Investigator-Initiated, Single-Center, Prospective Clinical Study - Durairaj, Kay; Baker, Omer; Yambao, Monalea; Linnemann-Heath, Jacob; Shirinyan, Ani (Aesthetic plastic surgery, 2024)
Background Cellulite is a condition characterized by dimpling and contour irregularities in the gluteal and thigh regions, affecting an estimated 80–98% of postpubertal women. Innovative treatments for cellulite dimpling in the buttocks have gained popularity in recent years, seeking new solutions for a historically challenging condition. In this open-label, investigator-initiated, single-center, prospective clinical study, the authors sought to evaluate the safety and efficacy of diluted calcium hydroxylapatite (CaHA; Radiesse®, Merz Aesthetics, Raleigh, NC) for the treatment of cellulite dimpling in the buttocks of adult women. Methods Subjects underwent three treatment sessions, receiving a total of 12 syringes of 1:1 diluted CaHA administered using a cannula-based subcision technique. Endpoints included the cellulite severity scale (CSS), the global aesthetic improvement scale (GAIS), subject satisfaction measured on a 5-point scale, and three-dimensional imaging analysis via the Quantificare 3D Track®. Results Twenty-four subjects completed the study (mean age, 35 years; mean BMI, 26.88 kg/m 2 ; mean body fat percentage, 31.29%), and no serious complications were reported. Quantitative analysis at week 14 revealed a mean reduction of 54.0% in the number of visible dimples and 50.09% in dimple depth compared to baseline. The mean CSS score decreased by 4.29 points, representing a 43.92% improvement in cellulite severity from baseline ( p < 0.0001). Both physician-assessed and subject-assessed GAIS ratings also demonstrated significant improvement, with 91.6% of subjects rating their cellulite appearance as “improved” or greater. Conclusion The results of this study support the safety and efficacy of diluted CaHA for treating cellulite dimpling in adult women. Level of Evidence II This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 . Clinical trials registration: This study is registered with clinicaltrials.gov (ID: NCT05885035) and can be found at this link: https://clinicaltrials.gov/study/NCT05885035 .